Efficacy of Laser Therapy in Patient Self-Assessment for Cervical and Lumbar Spine Pain Syndromes – Original Study - Ruta, Damian (Journal of Education, Health and Sport, 2024)
Introduction: Laser therapy, or Light Amplification by Stimulated Emission of Radiation (LASER), is a relatively popular method used in rehabilitation for various patient conditions. Purpose: To evaluate the effectiveness of laser therapy in treating pain syndromes of the cervical and lumbar spine. Material: The study included 108 patients, consisting of 72 women (67%) and 36 men (33%) diagnosed with chronic pain syndromes in the cervical and lumbar spine regions. The average patient age was 64.4 years. Method: A proprietary questionnaire survey Results: According to 44.4% of respondents, the effects of laser therapy are moderate, while 28.7% reported significant improvement. The study showed that for 50% of patients, the pain relief was substantial, for 37% it was minimal, and for only 9.3% there was no noticeable improvement. Among the participants, 70.8% of women and 75% of men considered laser therapy to be an effective treatment. Notably, 100 respondents expressed a willingness to undergo laser therapy again in the future. Conclusions: The data indicates that laser therapy is an effective treatment for spinal pain syndromes, often resulting in significant symptom relief. However, the concern is the short duration of pain relief after therapy, with symptoms commonly recurring within a few months to a year. The willingness of 100 respondents to undergo future laser therapy underscores the positive perception of this rehabilitation method among patients.